(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The protection of Geographical Indication has become a key IPR concern. This is because GIs usually have distinct characteristics that differentiate them, like such as taste, smell, and texture. This uniqueness also makes the GI goods vulnerable to infringement. Therefore, an effective legal system is essential in order to fully utilise on the commercial potential of GIs. This article aims to explore the challenges within the framework of Geographical Indications, while delving into the dispute of Darjeeling tea. The ‘Darjeeling’ tea remains in close association with the local communities and is made in the same way as it was made centuries ago. The word ‘Darjeeling’ tea and its logo have unauthorisedly been represented in multiple countries. It has not only created confusion among consumers but also led to damage tea’s goodwill and dilution of its brand image. The Tea Board India v ITC Limited case holds a significant position in Indian IP case history as the first case on geographical Indications in the country, decided by the Calcutta High Court. The Court acknowledged the significance of Geographical Indication (GI) and declined to issue an injunction against ITC Limited, the Defendant, for using the term ‘Darjeeling’ in ITC Calcutta’s lounge area.